2005
DOI: 10.1021/ct0499478
|View full text |Cite
|
Sign up to set email alerts
|

Activation of H−H, C−H, C−C and C−Cl Bonds by Pd and PdCl-. Understanding Anion Assistance in C−X Bond Activation

Abstract: To understand the mechanism of anion assistance in palladium-catalyzed H-H, C-H, C-C and C-Cl bond activation, several mechanistic pathways for oxidative addition of Pd and PdCl(-) to H2 (H-H), CH4 (C-H), C2H6 (C-C and C-H) and CH3Cl (C-Cl) were studied uniformly at the ZORA-BP86/TZ(2)P level of relativistic nonlocal density functional theory (DFT). Oxidative addition of the neutral, uncoordinated Pd atom proceeds, as reported earlier, via direct oxidative insertion (ΔH(⧧)298 is -22 to 10 kcal/mol), whereas st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 25 publications
10
139
1
Order By: Relevance
“…The Bickelhaupt group has applied the ADF-EDA scheme to a number of model alkane CH activation reactions (for select examples, see [61][62][63][64]). In one report, insertion transition states were analyzed for model CH activation reactions between methane and zero-valent group 2 (Be, Mg, and Ca) and group 12 (Zn and Cd) metals [61][62][63][64].…”
Section: [(Hbpym)ptcl]mentioning
confidence: 99%
See 2 more Smart Citations
“…The Bickelhaupt group has applied the ADF-EDA scheme to a number of model alkane CH activation reactions (for select examples, see [61][62][63][64]). In one report, insertion transition states were analyzed for model CH activation reactions between methane and zero-valent group 2 (Be, Mg, and Ca) and group 12 (Zn and Cd) metals [61][62][63][64].…”
Section: [(Hbpym)ptcl]mentioning
confidence: 99%
“…In one report, insertion transition states were analyzed for model CH activation reactions between methane and zero-valent group 2 (Be, Mg, and Ca) and group 12 (Zn and Cd) metals [61][62][63][64]. One motivation of this study was to provide an understanding based on transition state interactions why the lowest oxidation state of s-block main-group elements compared to Pd(0) have dramatically larger activation barriers for methane CH bond insertion.…”
Section: [(Hbpym)ptcl]mentioning
confidence: 99%
See 1 more Smart Citation
“…The whole mechanism could be described in three main steps [2,23]: (a) oxidative addition, (b) transmetalation, and (c) reductive elimination. Contrary to steps (a) and (c), that have been the subject of several experimental [24][25][26][27][28][29][30] and theoretical [31][32][33][34][35][36][37][38][39][40] studies less is known about the transmetalation process [41][42][43][44][45][46][47][48][49][50]. This is thus the most characteristic step of the cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported by Diefenbach et al that activated HAH bond length is equal to 1.383 Å . [41] Lows et al [42] and Rabaii et al [43] indicated that the length of HAH bond activation can reach even 2.14 and 2.79 Å , respectively. One would intuitively think that HAH bond length will decrease monotonously as the diameter of the nanotube increases and reach its equilibrium value inside the tube of larger diameter.…”
Section: H 2 (Jj)cntmentioning
confidence: 99%